2017
DOI: 10.1136/heartjnl-2016-311097
|View full text |Cite
|
Sign up to set email alerts
|

Persistent psychological distress and mortality in patients with stable coronary artery disease

Abstract: In patients with stable coronary artery disease, persistent psychological distress of at least moderate severity is associated with a substantial increase in CV and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 38 publications
1
36
0
4
Order By: Relevance
“…In patients of cardiovascular disease, several stressors have also been strongly related to cardiovascular endpoints, such as recurrent events and mortality. [61][62][63][64] In general, strong associations are less likely to be confounded than weak associations. For example, the 4.7-fold excess risk of cardiac event during anger outburst 60 could be explained away only if an unmeasured confounder was associated with both stress and cardiac event by as large hazard ratio as 9.0; a weaker uncontrolled confounding could not do so (Figure 2).…”
Section: Scale Of the Problemmentioning
confidence: 99%
“…In patients of cardiovascular disease, several stressors have also been strongly related to cardiovascular endpoints, such as recurrent events and mortality. [61][62][63][64] In general, strong associations are less likely to be confounded than weak associations. For example, the 4.7-fold excess risk of cardiac event during anger outburst 60 could be explained away only if an unmeasured confounder was associated with both stress and cardiac event by as large hazard ratio as 9.0; a weaker uncontrolled confounding could not do so (Figure 2).…”
Section: Scale Of the Problemmentioning
confidence: 99%
“…The possibility is real that CHD itself is the source of distress and a determinant of poor outcome. In fact, in the study by Stewart et al, 5 angina and dyspnoea increased progressively with the increase in the level of distress. Commonly, these symptoms are perceived as worrisome (and stressful) and as a harbinger of imminent risk (including the risk of death) in subjects experiencing them.…”
mentioning
confidence: 88%
“…The study by Stewart et al 5 found an increased risk of mortality only in subjects in the category of persistent moderate-to-high distress but not in subjects in lower distress categories. These results are not easy to reconcile with prior studies showing a dose–response relationship across all stress strata in which even low levels of stress were associated with increased risk of mortality 3.…”
mentioning
confidence: 94%
See 2 more Smart Citations